BUILDING DIGITAL CAPABILITIES OF CHILDREN'S FASHION SMES TOWARD INTERNATIONALIZATION: A QUALITATIVE CASE STUDY ON AK WEAR SMES - Wilyan Adisari; Sudarmiatin Sudarmiatin; Heri Pratikto (International Journal of Social Science, 2026)
Digital capabilities have now become a crucial prerequisite for Micro, Small, and Medium Enterprises (MSMEs) to survive and grow in the technology-driven global competition. This research aims to analyze the forms of digital capabilities possessed by AK Wear, a children's fashion MSME, and examine how these capabilities contribute to internationalization and export readiness. Additionally, this research identifies the challenges and opportunities in building digital capabilities toward the global market. The method used is a qualitative approach with a single case study design on AK Wear, where data was collected thru in-depth interviews and analyzed thematically. The research findings indicate that AK Wear has built a digital foundation thru intensive live selling practices, affiliate programs, and a presence on various platforms such as TikTok Shop, Shopee, and Instagram. However, there are significant obstacles such as low digital literacy among human resources, limitations in inventory management systems, and a strong dependence on platform algorithms. As a solution, this research proposes a phased strategic plan that includes internal strengthening in the short term, omnichannel integration in the medium term, and acceleration of exports and global brand strengthening in the long term. The results of this study provide practical implications for fashion SMEs in consolidating systems and digital competencies to achieve sustainable internationalization.